2006
DOI: 10.17660/actahortic.2006.719.29
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Cooling and Heat Recovery Using Fine Wire Heat Exchangers in a Closed Pot Plant Greenhouse: Design of an Energy Producing Greenhouse

Abstract: A greenhouse cooling system with heat storage for completely closed greenhouses has been designed, based on the use of a fine wire heat exchanger. The performance of the fine wire heat exchangers was tested under laboratory conditions and in a small greenhouse compartment. The effects of the system on the environmental conditions (temperature and humidity distribution) in the greenhouse were simulated to decide on the final lay out of the system. Finally the system was implemented on a large scale in a pot pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…This STE energy can be efficiently utilized with closed greenhouses (Bakker et al, 2006;Vadiee & Martin, 2012, 2013a. Yang et al (2012a) investigated the daily change of greenhouse indoor temperatures and designed a greenhouse system to utilize STE using a heat pump system, which recovers and stores STE and then supplies it when necessary.…”
Section: Al 2009mentioning
confidence: 99%
“…This STE energy can be efficiently utilized with closed greenhouses (Bakker et al, 2006;Vadiee & Martin, 2012, 2013a. Yang et al (2012a) investigated the daily change of greenhouse indoor temperatures and designed a greenhouse system to utilize STE using a heat pump system, which recovers and stores STE and then supplies it when necessary.…”
Section: Al 2009mentioning
confidence: 99%
“…neighbouring greenhouses or buildings. To achieve this, the performance of the greenhouse as a solar collector has to be maximized by 1): further reduction of the heat loss and 2): maximizing the heat collection by very efficient heat exchangers (Bakker et al, 2006). Simulations showed that with this system theoretically a year round heat production might be expected of about 800 MJ, comparable to the equivalence of 25 m 3 natural gas (de Zwart and Campen, 2005).…”
Section: Integral Design Of Energy Efficient Greenhouse Systemsmentioning
confidence: 99%
“…The function of the greenhouse as a solar collector is thereby maximized by further reduction of the heat loss from the greenhouse and maximizing the heat collection by much more efficient heat exchangers ( Fig. 4; Bakker et al, 2006). Currently in the Netherlands projects are set up with heat delivery from greenhouses to normal houses in so-called "energy grids".…”
Section: Integral Design Of Energy Efficient Greenhouse Systemsmentioning
confidence: 99%
“…Since the incoming solar radiation represents about twice the energy used in the greenhouse itself, this theoretically creates the possibility to use the greenhouse as a combined crop and heat producing system. The basic principle is a completely closed greenhouse from which the heat surplus during the summer is extracted by a cooling system, stored in a long term storage medium, and reused during the winter period for heating the greenhouse itself and neighbouring greenhouses or buildings (Bakker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%